What Makes the Olfactif of Victorian Literature? - Bojti, Zsolt (Hungarian Journal of English and American Studies, 2020)
Book review: Maxwell, Catherine. Scents and Sensibility: Perfume in Victorian Literary Culture. Oxford: Oxford UP, 2017. xviii + 361 pages. ISBN 978-0-19-870175-0. Hb. £30.00.